SISTEM PENDUKUNG KEPUTUSAN PEMBAGIAN TUNJANGAN HARI RAYA MENGGUNAKAN METODE FUZZY UNTUK KARYAWAN DI PT. KARIMUN MARINE SHIPYARD - Ahmad Dani; Zakwan Hilmy (Fakultas Sains dan Teknologi Universitas Karimun, 2023)
Work is a source of income for someone to fulfill the economy for themselves and their families. work is an activity that produces something and has value for others, in its implementation they must cooperate with a company or formal company. work is to get income in return for the energy expended. One of these incomes, apart from the basic salary, is the Hari Raya Allowance (THR). To get this holiday allowance, the researchers used fuzzy methods. and this research uses a kind of quantitative descriptive research method, research that collects data in the field using interview and observation techniques. The purpose of this research is to decide on the distribution of holiday allowance (THR) to the employees of PT. Karimun Marine Shipyard.